(untitled) (Indian Journal of Child Health, 2014)
Osteopetrosis or marble bone disease is a heterogeneous group of hereditary disorders in which deficient oraltered function of osteoclasts results into defective resorption of bone with resultant sclerosis. We report a caseof infantile osteopetrosis who presented to us as failure to thrive, severe anemia and developmental delay. Thiscase report highlights the importance of this rare disease as a differential diagnosis in infants with failure tothrive, to avoid the potentially treatable entity.